The undomestic goddess - Kinsella, Sophie (Black Swan, 2005)
The story of a girl who needs to slow down. To find herself. To fall in love. And to discover what an irons is for... Samantha is a high-powered lawyer in London. She works all hours, has no home life, and cares only about getting a partnership. She thrives on the pressure and adrenalin. Until one day... she makes a mistake. A mistake so huge, it'll wreck her career. She walks right out of the office, gets on the first train she sees, and finds herself in the middleof nowhere. Asking for directions at a big, beautiful house, she is mistaken for the interviewee housekeeper and finds herself being offered the job. They have no idea they've hired a Cambridge-educated lawyer with an IQ of 158-Samantha has no idea how to work the oven.